Analysis of Acoustical Characteristics and Some Recommendations for Different Educational Rooms - Valentın GÓMEZ ESCOBAR; Juan Miguel BARRIGÓN MORILLAS (Archives of Acoustics)
Acoustic parameters were analysed in nine auditoria and multi-purpose confer- ence rooms in the University of Extremadura. Parameters related to the reverber- ation time, background noise, and intelligibility (both physical measurements of different parameters [Definition (D-50) and STI] and speech tests used to study the subjective response of listeners) were studied. The measurements were compared with some recommendations from the literature and, considering that speech was the main use of the studied rooms, with the intelligibility results. Some different recommendations for reverberation times taken from the literature were analysed. The intelligibility results obtained from the measurements were also compared with the intelligibility results that were determined by the speech tests.